Corruption and bureaucratic structure in a developing economy - John Bennett; Saul Estrin (Institute for the Study of Labor (IZA), 2006)
We address the impact of corruption in a developing economy in the context of an empirically relevant hold-up problem - when a foreign firm sinks an investment to provide infrastructure services. We focus on the structure of the economy's bureaucracy, which can be centralized or decentralized, and characterize the 'corruptibility' of bureaucrats in each case. Results are explained in terms of the non-internalization, under decentralization, of the 'bribe externality' and the 'price externality.' In welfare terms, decentralization is favoured, relatively speaking, if the tax system is less inefficient, funding is less tight, bureaucrats are less venal, or compensation for expropriation is ungenerous.
Keywords: D73; H11; H77; 330; corruption; bureaucratic structure; developing economy; Korruption; Bürokratie; Privatisierung; Theorie